The Use of Computer Tools in Assessing the Development of Learning Interactions in Primary Schoolchildren - Konokotin A.V (Moscow State University of Psychology and Education, 2021)
The article presents results of a study on the possibilities of using the 'Scales' research technique for assessing the effectiveness of learning interactions in primary school children. The study involved 90 students of primary school (N=90), grades 1 to 4. We discuss the issue of using computer tools in activity- based assessments. In our study, we have implemented the fundamental theoretical principle, according to which the very nature of participants' activities determines the structure of the digital system construction. We show that evaluating the effectiveness of learning interactions in joint problem-solving tasks is possible in situations when the 'digital shell' of the students' activities becomes a means to actualize the processes of communication, exchange of actions, mutual understanding and reflection, which determine the process of setting the learning task and finding the generalised way of solving it. It is noted that in the course of solving experimental problems, there is a qualitative change in these processes, which are an integral characteristic of the sense of community that arises between children and adults and, in turn, allows children to reach beyond the framework of the current subject problem and to move over to meaning-based interactions (Z=-3.651, Asympt.Sig.(2-tailed)<0.001, p=0.05).